Peningkatan Pengetahuan Remaja melalui Edukasi Gizi terkait Label Pangan - Putra, Muh Guntur Sunarjono; Amrinanto, Ahmad Hisbullah; Nuria, Ririn; Nirmalarani, Yayie; Marscella, Okada (Yumary: Jurnal Pengabdian kepada Masyarakat, 2024)
Purpose: This nutrition education aims to increase public awareness, especially among teenagers, regarding how to read food and nutrition labels, influencing teenagers' attitudes regarding appropriate food consumption patterns to reduce the risk of nutritional problems, significantly overweight and obesity. Research methodology: Community Service with the topic of food labels for adolescents was held in class XI Multimedia, Kusuma Wardhana Vocational High School, on Thursday, February 1, 2024, attended by 27 subjects or students. The series of Community Service activities include giving pre-test questions, delivering material related to how to read food labels and the impact of consuming instant food and other packaged processed foods over a long period, and ending with giving post-test questions. The tools used in this activity consist of material in the form of power points and examples of packaging products. Results: This educational activity can increase the subject's knowledge score regarding how to read food labels and the impact of consuming instant food and other packaged processed foods over a long period before the post-test score (after being given education) is 33.0 points greater than the pre-test score (before being given education). Limitations: The limited number of subjects means that the results of this education cannot be subjected to statistical analysis, and there needs to be more variety in the educational media used. Contribution: This nutritional education can increase awareness among teenagers and increase awareness of the importance of reading food labels, which impacts regulating food consumption patterns.